Pretransplantation seroreactivity in kidney donors and recipients as a predictive factor for posttransplant BKPyV-DNAemia - Saláková, Martina; Ludvíková, Viera; Hamšíková, Eva; Kolářová, Marie; Šroller, Vojtěch; Viklický, Ondřej; Wohlfahrtová, Mariana (Frontiers in Immunology, 2022)
BK polyomavirus (BKPyV) often reactivates after kidney transplantation, causing BKPyV-associated nephropathy (BKPyVAN) in 1–10% cases with potential detrimental effect on allograft survival. Kidney recipients are regularly screened to detect BKPyV DNA in blood and urine after renal transplantation. However, this strategy may not always reduce the risk of developing BKPyVAN and other predictive markers are needed. To evaluate the role of pretransplant BKPyV specific antibody, 210 kidney transplant recipients and 130 donors were screened for the presence of BKPyV DNA and BKPyV specific antibody. We found that donor BKPyV IgG seroprevalence and antibody level was strongly associated with BKPyV viremia and BKPyVAN; however, multivariant analysis found the presence of anti-BKPyV specific antibodies as a predictive factor only for BKPyV viremia. The pretransplant status of the recipients had no effect on posttransplant BKPyV viremia and BKVAN. BKPyV IgG levels in recipients without BKPyV infection remained stable during one-year follow-up, while a considerable increase was observed in viremic and viruric recipients. The determination of specific BKPyV antibodies in kidney allograft donors represent a good and reliable predictive marker for posttransplant BKPyV replication and risk stratification in transplant recipients.